Simple Lie algebras over fields of positive characteristic. - Strade, Helmut, 1942- (De Gruyter expositions in mathematics ;, 2004)
The problem of classifying the finite-dimensional simple Lie algebras over fields of characteristic p & 0 is a long-standing one. Work on this question during the last 35 years has been directed by the Kostrikin-Shafarevich Conjecture of 1966, which states that over an algebraically closed field of characteristic p & 5 a finite-dimensional restricted simple Lie algebra is classical or of Cartan type.